Mortality Pattern of Hospitalized Children in A Tertiary Care Hospital in Latur: A Record Based Retrospective Analysis - Sachin W Patil; Lata B Godale (Medsci Publications, 2013)
Problem statement: Children mortality is one of very important indicators which reflect country's development. In country like India, causes of children mortality are often poorly documented in most of the hospitals. The present study aimed at finding the major causes childhood mortality of inpatients in the Pediatric Department admitted during September 2011 to august 2012. Methods: A retrospective analysis was done with the medical records of Childrens died in the Peadiatric Department of Government Medical College and Hospital, Latur, from 1 September 2011 to 31 August 2012. Results- A total of 3910 children were admitted to the Pediatric Department during study period. Total 176 paediatric deaths, 61.15% males and 38.84% females, were recorded. Out of total 176 pediatric deaths, 57.95 % were Neonatal deaths. Among the 139 infant deaths, neonatal deaths were 74%. Birth Asphyxia was most common cause for neonatal deaths while sSepticemia was the leading killer in post neonatal infants. Conclusion-The childhood mortality pattern in different age groups suggests that we are in need of an effective and more comprehensive improvement in maternal health care along with antenatal and newborn care.